Compton radiation of an electron in the field of running plane linear polarized electromagnetic wave - Drebot, I.; Grigor'ev, Yu.; Zelinsky, A. (Вопросы атомной науки и техники, 2009)
Results of integration of Lorentz force equation for a relativistic electron, moving in the field of running, plane, linear polarized electromagnetic wave are presented in the paper. It is shown that electron velocities in the field of the wave are almost periodic functions of time. Expansion of the electromagnetic field in a wave zone into generalized Fourier series was used for calculations of angular spectrum of electron radiation intensity. Expressions for the radiation intensity spectrum are presented in the paper. The derived results are illustrated for electron and laser beam parameters of NSC KIPT X-ray generator NESTOR. Simultaneously, derived expressions give possibilities to investigate dependence of energy and angular Compton radiation spectrum on phase of interaction and the interacting wave intensity. Приведены результаты интегрирования уравнения Лоренца для релятивистского электрона, движущегося в поле бегущей плоской линейно поляризованной электромагнитной волны. Показано, что скорость электрона в поле такой волны является почти периодической функцией времени. Для расчета углового спектра интенсивности излучения электрона было использовано разложение электромагнитного поля в волновой зоне в обобщенный ряд Фурье. Выражения для интенсивности спектра излучения представлены в работе. Полученные результаты иллюстрируются для параметров электронного и фотонного пучков источника рентгеновского излучения ННЦ ХФТИ "НЕСТОР". В то же время, полученные выражения дают возможность исследовать зависимость энергетического и углового спектров комптоновского излучения от фазы взаимодействия и интенсивности взаимодействующей волны. Приведено результати інтегрування рівняння Лоренца для релятивіського електрона який рухається в полі бігучої плоскої лінійно поляризованої електромагнітної хвилі. Показано, що швидкість електрона в полі такої хвилі є практично періодична функція часу. Для розрахунку кутового спектра інтенсивності випромінювання електрона було використано розклад електромагнітного поля в хвильовій зоні в узагальнений ряд Фур'є. Вирази для інтенсивності спектра випромінювання представлені в роботі. Отримані результати ілюструються для параметрів електронного та фотонного пучків джерела рентгенівського випромінювання ННЦ ХФТІ "НЕСТОР". У той же час, отримані вирази дають можливість досліджувати залежність енергетичного та кутового спектрів комптонівського випромінювання від фази взаємодії та інтенсивності хвилі що взаємодіє.